Iodine-catalyzed Friedel-Crafts alkylation of electron-rich arenes with aldehydes: efficient synthesis of triarylmethanes and diarylalkanes - Jaray Jaratjaroonphong (2018)
Iodine is shown to be an efficient catalyst for the Friedel-Crafts alkylation of arenes with a wide variety of aldehydes in toluene under 'open-flask' and mild conditions. In the presence of 10 mol % of iodine, the reaction of arenes with aromatic aldehydes gives the corresponding triarylmethane derivatives (TRAMs), regioselectively, in good to excellent yields. On the other hand, a series of diarylalkane derivatives is synthesized smoothly by the reaction with aliphatic aldehydes. © 2009 Elsevier Ltd. All rights reserved.